Acute Acalculous Cholecystitis and Small Bowel Obstruction: A Case Report and a Review of the Literature (Global Journal of Medical Research, 2016)
We present a case of a 73-year-old male presenting with abdominal pain. He presented with what was suggestive of a small bowel obstruction secondary to an incarcerated inguinal hernia. Subsequent investigation after operative management of the hernia denoted that it was all secondary to acalculous cholecystitis; we thus present our case and pitfalls in management.